Das heilige Tor evangelisches Religionsbuch - Heuer, Reinhard; Kegel, Martin; Boysen, M.; Schütz, R.; Schäfer, Rudolf (Ferdinand Hirt, 1931)
Das Frontispiz ist eine s/w-Abbildung der Zeichnung "Das ewige Licht" von Rudolf Schäfer